The Application of Coooperative Learning Model TPS (Think Pair Share) Type for Increasing Activities and Students Achievment X IPA 1 SMA Negeri 3 Jember - Teripena E C (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Mathematics is study materials that has abstract object and built base on the proces deducattive reasoning,it is the truth of concep that is goinet as the logic result from the thruth before after being got.In mathe matics approach learning it is easy to be understood by students,The proces deducative reasoning is used for strengthened the comprehension that have been owned by students.The purose of mathematics learninng is to practice way of systematic,logics,creative and consistent thinking. The problems of this research are : (a) How to increase the students’achicument learning by the application cooperative learning method of TPS model? (b)What is the effect between cooperative leaarning model method of TPS model and student’learning motivation. The purose of this research are: (a) To know of this increasing of student learning achievement after being applied the learning cooporative method model of TPS.(b) To know the effect of students learning motivation after having been applied the learning methd model of TPS. Thr reasearch uses action research for three cycles. Every cycle consists of four steps. They are drafting and obsrvation,reflection an revision. The targe study is the students of X IPA1 SMAN 3 Jember. The data is gained from the result of formative test,teaching leaarning observation sheet.. The result of the research is the students achievement increase from first cycle up second cycle.They are 45,16% for the first cycle with 17 students that are incomplete and the second cycle it reaches 83,87% with 5 student incomplete. The reseach conclusion is cooprative method model TPS can effesct positively to students’ learning motivation to understan the chance of material concept so the students can reach the maximum chievmen and this learning model can used as the one of alternative mathematics learning so teaches can give this mathematics material concept more to the students.